Thuật toán giải bài toán điều khiển tối ưu với rang buộc dạng Alternative - Hà, Vũ Thanh (Journal of Computer Science and Cybernetics, 2016)
This paper is decribed in great detail algorithm for maximizing the subject function of the discrete control system with the alternative constrains following final points. The algorithm is based on the plan notion that is firstly proposed by R. Garbasov and F.M. Kirillova in linear programming.